2020
DOI: 10.1080/21670811.2020.1813047
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of “Incidental News Consumption”: an Eye Tracking Study of News Interaction on Facebook

Abstract: We thank Carolina Carazo, Amy Ross, the anonymous reviewers, and the journal's editors for their most helpful comments on previous versions of this manuscript. We also thank Brayan Rodríguez and Larissa Tristán for their help in conducting the research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Long videos and use of background music were negatively associated with receiving likes and comments. This is possibly because audiences spend very little time—less than 6 s—on news they usually encounter versus seek on Facebook (Vergara et al, 2021). Long videos and background music require a level of engagement users aren’t usually prepared to provide when scrolling through their newsfeed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long videos and use of background music were negatively associated with receiving likes and comments. This is possibly because audiences spend very little time—less than 6 s—on news they usually encounter versus seek on Facebook (Vergara et al, 2021). Long videos and background music require a level of engagement users aren’t usually prepared to provide when scrolling through their newsfeed.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of video style, Kim and Yang (2017) found that posts with photos and videos positively predicted “shares” and posts with photos increased “likes” from audiences but not necessarily comments. A recent eye-tracking study found that videos and photos were the entry point to audiences’ engagement with a news-related Facebook post (Vergara et al, 2021). The study did not examine the kind of visual elements and imagery included in the posts which we accounted for in our research.…”
Section: Variablesmentioning
confidence: 99%
“…Another core aspect of articles' presentation refers to heuristic cues such as headlines, teasers, source cues and visuals. Visuals usually serve as triggers for more indepth engagement with news (Vergara et al, 2020). But they can also drive clicks despite no significant interest in the topic (Groot Kormelink and Costera Meijer, 2018).…”
Section: Presentational Factorsmentioning
confidence: 99%
“…Over time, each of these shows’ Facebook pages became digital places (Gutsche and Hess, 2020a) for exploring and explaining medical and scientific meanings associated with the lockdown and their pages’ significant social value. And there, commenters – whether trolling (Wolfgang, 2018), interacting through incidental media use (Vergara et al, 2020), or commenting as regular contributors to the pages – recalled traditional and long-lasting normative standards of journalism with which they analyzed the journalistic aspects of these “soft news" -- programs. For example, on one BBC Breakfast’s Facebook page post featuring “person-on-the-street” videos about their opinions on government regulations, users commented that the reporting lacked depth: “Very disappointed with BBC breakfast … can’t help feeling disappointed with your flower power news and little questioning of the government extremely sad” (BBC, 2020a).…”
Section: Introductionmentioning
confidence: 99%